Ionization of organic molecules with metal ions formed in the laser plasma. (4th April 2021) - Filatov, Vasily V.; Nikiforov, Sergey M.; Zelenov, Vladislav V.; Pento, Andrey V.; Bukharina, Aygul B.; Sulimenkov, Ilia V.; Brusov, Vladimir S.; Yu, Jiajun; Kozlovskiy, Viacheslav I.
Abstract: A laser plasma ion source was used to ionize volatile organic compounds in a gas sample. The plasma was generated on a metal target in the intermediate vacuum region of ~0.3 Torr using a pulsed Nd:YAG laser with a wavelength of 1 μm. The resulting ions mass spectra were acquired using orthogonal time‐of‐flight mass spectrometer (O‐TOF MS). When using a copper target, the ions formed are simple complexes (CuM + ) of copper ions with organic molecules. The possibility of online identification of trace amounts of alkanes in nitrogen and air, with a detection limit of ~10 ppb, was demonstrated. The ionization efficiency of volatile organic compounds through the formation of clusters with metal ions is 10 −4 in terms of the quasimolecular complex ions. The rate constants of ion‐molecular reactions of copper ions with octane and water molecules in nitrogen and air are estimated.